Case-Based Reasoning as a Heuristic Selector in a Hyper-Heuristic for Course Timetabling Problems - Petrovic, Sanja; Qu, Rong (IOS Press, 2002)
This paper studies Knowledge Discovery (KD) using Tabu Search and Hill Climbing within Case-Based Reasoning (CBR) as a hyper-heuristic method for course timetabling problems. The aim of the hyper-heuristic is to choose the best heuristic(s) for given timetabling problems according to the knowledge stored in the case base. KD in CBR is a 2-stage iterative process on both case representation and the case base. Experimental results are analysed and related research issues for future work are discussed.